Value chain model of data governance and its application on data governance regulation analysis - Keman HUANG; Xiaoyong DU (大数据)
Cultivating the data marketplace is an important mechanism to achieve the value of big data.The prosperity of such a data marketplace needs a sustainable and healthy data service ecosystem.A data governance value chain model was developed to identify the primary and support activities for data value release.Then the data service ecosystem model was implemented accordingly to distinguish different stakeholders and their core functions that a data marketplace should have.Using the developed data governance value chain model and data service ecosystem model, the data dovernance regulation was analyzed systematically, aiming at providing suggestions to promote the growth of the data marketplace.